The Effect of Red Fruit Oil (Pandanus conoideus) to the Histophysiology of Rat (Rattus norvegicus) Liver Exposed to Cigarette Smoke - Kio, Albertina Dhiu; Saraswati, Tyas Rini; Yuniwarti, Enny Yusuf Wachidah (Biosaintifika: Journal of Biology & Biology Education, 2018)
Free radicals in cigarette smoke may interfere the balanced of body molecules and cause the damage of hepatic cells. This issues may be prevented by using red fruit oil (Pandanus conoideus L) due to its antioxidant content. This study aimed to evaluate the structure and physiological conditions of liver when the red fruit oil given to the rat that exposed by cigarette smoke. This study carried out for 35 days with female white rats as the sample. The samples were 20 female white rats divided into four groups: P0 (negative control), P1 (positive control), P2 (exposed by cigarette smoke with administration of red fruit oil 0,1 ml/BB), P3 (exposed by cigarette smoke with administration of red fruit oil 0,2 ml/weight). The data of ALT, AST, cell diameter, and hepatic weight were analyzed by using analysis of variants (ANOVA). The results showed that administration of red fruit oil containing antioxidants can reduce levels of ALT, AST, hepatocyte diameter, and increase liver weight, although the difference is not significant compared to the control group and does not affect the eating and drinking behavior so as not to affect the bodys metabolism. The conclusion of red fruit oil can reduce ALT, AST, hepatocyte diameter and increase hepatic weight due to exposure to cigarette smoke, although the difference is not significant to the control group, and does not affect the eating and drinking behavior, so good for consumption because it gives a beneficial effect on health liver organ.